1986
DOI: 10.1002/aic.690320707
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of turbulent mass transfer at a mobile interface

Abstract: Numerical solutions to the unaveraged mass balance equation for the case of a flat mobile interface reveal that both high-and low-frequency velocity fluctuations can contribute to mass transfer. This is in contrast to transport to a solid boundary where only low-frequency fluctuations, normal to the wall, are important. The average mass transfer coefficient is found to depend on Schmidt number to the -0.5 power, in agreement with classical theories. It is related to the velocity field in the liquid primarily t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 7 publications
9
86
0
3
Order By: Relevance
“…For low to moderate R T it was also found that K L /u ∞ ∝ R − 1 /2 T . The above is in agreement with the large eddy model of Fortescue & Pearson (1967), A direct comparison of K L obtained in the DNS-s and several grid-stirred experiments with the surface divergence model of McCready et al (1986) showed a very good agreement when using a constant of proportionality of 0.525.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…For low to moderate R T it was also found that K L /u ∞ ∝ R − 1 /2 T . The above is in agreement with the large eddy model of Fortescue & Pearson (1967), A direct comparison of K L obtained in the DNS-s and several grid-stirred experiments with the surface divergence model of McCready et al (1986) showed a very good agreement when using a constant of proportionality of 0.525.…”
Section: Discussionsupporting
confidence: 65%
“…Laboratory measurements have indeed shown β rms to be a good measure for mass transfer as it implicitly takes the surface conditions into account (Turney & Banerjee 2013). Figure 9 shows the dependency of K L on the surface divergence supporting the surface divergence model of McCready et al (1986), K L ∝ √ β rms D. It can be seen that our numerical results predict that K L = 0.525 √ β rms D which matches the trend of the experimental results in grid-stirred tanks performed by Herlina & Jirka (2008); McKenna & McGillis (2004a). The advantage of the present numerical simulation is that surface contamination is not an issue so that unbiased investigations of the effect of Sc and the turbulence levels (here described in terms of the turbulent Reynolds number R T ) can be performed.…”
Section: Transfer Velocitymentioning
confidence: 93%
See 2 more Smart Citations
“…Theofanous et al (1976) proposed two regimes, in which the large-eddy model is valid for low R T and the small-eddy model is valid for high R T , where the critical R T is approximately 500. Another conceptual model is the surface divergence model, originating from the numerical investigation by McCready, Vassiliadou & Hanratty (1986 Kermani et al 2011;Herlina & Wissink 2014) confirmed that surface divergence provides a good measure for the transfer velocity, as surface conditions are implicitly taken into account. Recently, however, Turney & Banerjee (2013) found that the surface divergence model is not applicable when a portion of the near-surface motions hold small time scales.…”
mentioning
confidence: 99%